Steroid Cell Tumour in Pregnancy: Reflection on a Rare Case and Review of the Literature - J. Weishaupt; U. Herbst (Case Reports in Obstetrics and Gynecology)
There are only a few cases of steroid cell tumours that have been described in the literature. Here, we present an exceptionally rare case of a steroid cell tumour arising from the ovary in early pregnancy.